WOMAN VIOLENCE AND RESISTANCE IN “SWEAT” SHORT STORY BY ZORA NEALE HURSTON: FEMINIST APPROACH - Noviana Osinta Bere; Tomi Arianto (BASIS (Bahasa dan Sastra Inggris), 2019)
Zora Neale Hurston’s short story is a story of women with different perspective. This revealed the violence toward women and women’s resistance toward the construction of patriarchal. The violence was shown by a husband toward his wife in psychological, physical and sexual form. The theory used Beauvoir‘s theory (2012). The researcher analyzed the problem in feminist approach. Women who experience oppression took the resistance as a form of struggle over their existence as women. It was reflected toward the main character in this short story. This descriptive qualitative research was used in this short story. This method was used for looking at data contexts that were hidden from quotations in a short story. The findings showed that Delia was able to resist her husband named Sykes. Delia sought her freedom by escaping the scandal the cruel treatment of her husband. Delia’s action contradicted with patriarchal construction that women had to be submissive and respectful towards men due to the women basically were dependent on men. Feminism appeared in this short story was concerned on women’s resistance toward violence experienced in social life in order to get freedom, rights and opportunities as a human.